Engineering entertainment. - Karlin, S. (IEEE spectrum)
This paper describes how electrical engineers with the skill to handle interactive TV and integrated media are in high demand. It describes how entertainment industry work has more to do with traditional engineering and computer programming than with, say, computer graphics or multimedia. A knowledge of network management, TCP/IP protocols, and servers, switchers, and routers comes in handy. Familiarity with set-top box technology is also key